Caracterização molecular de bactérias isoladas de lagoas salinas do norte do Perú e avaliação do potencial de novas biomoléculas frente a diferentes tipos de células tumorais : Molecular characterization of bacteria the lagoons of northern and evaluation of potential of new biomolecules against different types of tumor cells - Clavo, Rene Flores, 1986- (2017)
Orientador: Fabiana Fantinatti Garboggini